Variant Molar Mass and Concentration Effect of Polyethylene Glycol over the Physico-Chemical Behaviour of CTAB and SDS - Ali1, Hazrat; Khan1, Azim; Ullah2, Irfan; Fatima Durrani1, Gulrez; Kaleem Baloch2, Musa; Rauf3, Abdur; Niazi1, Ayesha; Akram4, Muhammad (Asian Journal of Chemistry, 2014)
Ionic surfactant such as sodium dodecylsulfate (SDS) and N-cetyl N,N,N-trimethyl ammonium bromide (CTAB) has been tensiometrically and conductometrically studied in the presence and absence of water soluble polymer i.e., varying concentration and molar mass of poly(ethylene glycol). Surface tension study shows that poly(ethylene glycol) (PEG) is surface active and its mixture with CTAB and SDS effect the CMC of these surfactants i.e., CMC of CTAB increases with addition of PEG, changes more when concentration or molar mass increases while the effect is opposite for SDS. The surface tension curve of the mixed system of CTAB-PEG show that after CMC, CTAB molecules replace all the PEG molecules or its loops while in case of SDS-PEG some molecules or loop of the polymer always been present at the interface beyond CMC of SDS. Thermodynamic parameters calculated for the mixed systems shows that free energy of micellization for CTAB-PEG increases with the increase in concentration and molar mass of polymer, but opposite result was observed for SDS-PEG mixture. The conductometric and tensiometric results, regarding micellization were comparable. Whereas, different micellization behavior of CTAB and SDS in the presence of PEG is due to the hydrophobic interaction and ion dipole interaction between CTAB-PEG and SDS-PEG, respectively.